Policy priorities in diabetes care: a Delphi study. Issue 1 (March 1996) - Gallagher, M; Bradshaw, C; Nattress, H
Abstract : OBJECTIVES–To produce policy priorities for improving care of diabetes based on the findings of original research into patient and professional opinions of diabetes care in South Tyneside. To judge the feasibility of implementing these priorities as policy. DESIGN–A two round Delphi survey with a panel of 28 ¿experts.¿ In the first round each respondent produced a list of recommendations based on the findings of a report of patients' and professionals' opinions of diabetes care. 20 respondents produced a total of 180 recommendations, reviewed by a monitoring panel to produce a summary list of 28 recommendations. In the second round respondents rated each recommendation on two 5 point Likert scales. SETTING–Mainly Tyneside but also other parts of England. SUBJECTS–28 healthcare professionals, including patients and patients' representatives. MAIN MEASURES–Voting by experts on how important each recommendation was to improving diabetes care service, and how likely the recommendation was to be implemented in the next five years. RESULTS–There was a high degree of consensus among respondents about recommendations considered important and likely to be implemented–namely, those concerned with improving communications between doctors in hospital and in general practice, and improving communications with patients. Respondents were more pessimistic about the prospects of implementing the recommendations than about their importance. Respondents thought that standards were important for improving care, and half would stop payments to general practice diabetic clinics that did not keep to district standards for diabetes care. For two recommendations a mismatch occurred between the importance of the recommendations and likelihood of implementation. This may reflect the practical problems of implementing recommendations. 18 of the 22 respondents thought that the study was useful in generating recommendations. CONCLUSIONS–The Delphi technique is a useful method for determining priorities for diabetes care and in assessing the feasibility of implementing recommendations.